2005
DOI: 10.1093/humrep/dei359
|View full text |Cite
|
Sign up to set email alerts
|

In unselected patients, elective single embryo transfer prevents all multiples, but results in significantly lower pregnancy rates compared with double embryo transfer: a randomized controlled trial

Abstract: To avoid twin pregnancies resulting from an IVF treatment, eSET should be applied in all patients. The consequence would be a halving of the ongoing PR as compared with applying a DET policy in all patients. The transfer of one embryo in a selected group of good prognosis patients leads to a less drastic reduction in PR but maintains a twin PR of 12.9%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
120
2
11

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(138 citation statements)
references
References 23 publications
3
120
2
11
Order By: Relevance
“…Clearly, eSBT must be applied selectively to a good prognosis cohort. Randomized prospective trials have demonstrated that, in an unselected patient population, eSET can significantly compromise PR [30]. Our results suggest, however, that age alone should not automatically prevent inclusion in a good prognosis cohort.…”
Section: Discussionmentioning
confidence: 60%
“…Clearly, eSBT must be applied selectively to a good prognosis cohort. Randomized prospective trials have demonstrated that, in an unselected patient population, eSET can significantly compromise PR [30]. Our results suggest, however, that age alone should not automatically prevent inclusion in a good prognosis cohort.…”
Section: Discussionmentioning
confidence: 60%
“…Finally, we applied observed age-specific probabilities of going on to subsequent frozen cycles following failed frozen cycles, and assumed that these probabilities would be the same following eSET and DET. 28,29 Age-specific discontinuation rates following completed treatment cycles (i.e. fresh cycles with associated frozen/thawed cycles) were also estimated from the clinical data set and the same rates were applied for eSET and DET.…”
Section: Linking Cyclesmentioning
confidence: 99%
“…Six RCTs, comparing forms of SET with DET in, generally, patients with a good prognosis, 10,[12][13][14][15][16][17][18] and a Cochrane review 6 have been undertaken. SET alone gave poorer outcomes in terms of live birth rate per embryo transfer cycle but reduced the incidence of twins to a rate comparable with natural pregnancies.…”
Section: Elective Single Embryo Transfer Trialsmentioning
confidence: 99%
“…Most of the trials explicitly included only good prognosis patients, and beyond this it is to be expected that better prognosis patients would be more likely to consent to participate in a trial, as shown by comparisons between those who consented and those who refused in two of the trials. 14,18 It is also generally accepted that patients in clinical trials have better outcomes than is routine.…”
Section: Comparison With Data From Randomised Trialsmentioning
confidence: 99%